THE EFFICACY OF NITROFURANTOIN FOR CHILDREN WITH ACUTE CYSTITIS CAUSED BY EXTENDED SPECTRUM ?-LACTAMASE PRODUCING ESCHERICHIA COLI - Kara, Aslihan; Gurgoze, Metin Kaya (Springer, 2018)
[Abstract Not Available]